Price-setting in the foreign exchange swap market: Evidence from order flow - Olav Syrstad; Ganesh Viswanath-Natraj (Norges Bank, 2020)
This paper investigates price discovery in foreign exchange (FX) swaps. Using data on inter-dealer transactions, we find that a 1 standard deviation increase in order flow (i.e. net pressure to obtain USD through FX swaps) increases the cost of dollar funding by up to 4 basis points after the 2008 crisis. This is explained by increased dispersion in dollar funding costs and quarter-end periods. We find central bank swap lines reduced the order flow to obtain USD through FX swaps, subsequently affecting the forward rate. In contrast, during quarter-ends and monetary announcements we observe high frequency adjustment of the forward rate.
hdl:11250/2690236
Keywords: E43; F31; G15; 330; interest rate parity; exchange rates; currency swaps; order flow; dollar funding